The Model Development of Online Talaqqi Quran Teaching: A Need Analysis - Nur Madiha binti Abdullah; Muhammad Hafiz Saleh; Siti Fatimah Mohd Tawil (USIM Press, 2024)
Journal of Quran Sunnah Education and Special Needs (JQSS) Volume 7 Issue 2 Page (108-121)